Internal medicine residents’ achievement goals and efficacy, emotions, and assessments - Daniels, Lia; Daniels, Vijay (Revue canadienne de l’éducation médicale, 2018)
Background: Achievement goal theory is consistently associated with specific cognitions, emotions, and behaviours that support learning in many domains, but has not been examined in postgraduate medical education. The purpose of this research was to examine internal medicine residents’ achievement goals, and how these relate to their sense of self-efficacy, epistemic emotions, and valuing of formative compared to summative assessments. These outcomes will be important as programs transition more to competency based education that is characterized by ongoing formative assessments. Methods: Using a correlational design, we distributed a self-report questionnaire containing 49 items measuring achievement goals, self-efficacy, emotions, and response to assessments to internal medicine residents. We used Pearson correlations to examine associations between all variables. Results: Mastery-approach goals were positively associated with self-efficacy and curiosity and negatively correlated with frustration and anxiety. Mastery-approach goals were associated with a greater value for feedback derived from annual ACP exams, end-of-rotation written exams, and annual OSCEs. Performance-approach goals were only associated with valuing ACP exams. Conclusion: Mastery-approach goals were associated with self-efficacy and epistemic emotions among residents, two constructs that facilitate autonomous learning. Residents with mastery-approach goals also appeared to value a wider range of types of assessment data. This profile will likely be beneficial for learners in a competency-based environment that involves high levels of formative feedback.